Effects of music on sleep quality among elderly people with hypertension: A randomised controlled trial - Elisabeth Wahyu Savitri; Florida Listavia Panggus; Yustina Riki Nazarius; Rita Purnamasari (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Hypertension is a condition in which an individual has persistently high blood pressure with systolic blood pressure > 140 mmHg and diastolic blood pressure > 90 mmHg when measured at least twice under two different conditions with a two-week interval. The causes of hypertension are broadly categorized into two risk factors: non-modifiable and modifiable. The prevalence of hypertension is still relatively high in both developed and developing countries, with a prevalence of 35% in developed countries and 40% in developing countries among the adult population. The highest prevalence of hypertension is found in the United States, at 46% of the adult population. It is estimated that 1 billion people worldwide suffer from hypertension, and it is predicted that by 2025, around 29% of the global population will have hypertension.Purpose: To understand the community's perspective on the importance of improving sleep quality through listening to classical music among individuals with hypertension.Method: This qualitative research employed a case study approach, focusing on describing and understanding phenomena in the social world and the perspectives of individuals with experience. The study concentrated intensively and in detail on cases of patients with hypertension experiencing sleep quality disturbances. The research was conducted on hospital patients in Pontianak City from June 23 to 26, 2023, with a total of two respondents, and it was carried out at the respondents' homes. Data collection utilized purposive sampling through interviews, observations, and documentation over three days. The inclusion criteria were patients with a diagnosis of hypertension, stable medical conditions, compos mentis consciousness, and sleep quality disturbances. The exclusion criteria were non-cooperative patients and their families, no comorbid diseases, and patients unable to communicate in Indonesian.Results: It was found that all hypertensive patients were elderly. Both hypertensive patients at Perumnas 1 Community Health Center were female. Respondents' systolic blood pressure ranged from 140-159 mmHg or higher, and diastolic blood pressure ranged from 90-99 mmHg, indicating that women are more prone to stress. Psychologically, women have lower coping mechanisms than men in dealing with problems. If there are physical and psychological disturbances, women will experience more severe sleep disturbances than men. There was an improvement in sleep quality after classical music therapy was administered to patients with sleep quality disturbances. Therefore, classical music therapy is effective and can be utilized by individuals such as nurses or healthcare workers in Perumnas 1 Community Health Center, Pontianak City, for the advancement of nursing and healthcare knowledge.Conclusion: Appropriate classical music can have an impact on the sleep quality of elderly individuals suffering from hypertension in Pontianak City in 2023.